Phylogenetic Reconstruction of the Ancestral Chromosome Number of the Genera Anochetus Mayr, 1861 and Odontomachus Latreille, 1804 (Hymenoptera: Formicidae: Ponerinae) - Afonso Neto, Paulo C.; Micolino, Ricardo; Cardoso, Danon Clemes; Cristiano, Maykon Passos (Frontiers in Ecology and Evolution, 2022)
Recent phylogenetic and molecular data are changing our knowledge about the relations between species and evolutionary processes resulting in the chromosome variation observed in ants (Hymenoptera: Formicidae). Ants exhibit remarkable variations in morphology, behavior, karyotypes, and chromosome structure. By assembling genetic and chromosome information about the trap-jaw ants from the subfamily Ponerinae, we reconstructed the phylogenetic relationships that inferred the monophyletic condition between the Anochetus and Odontomachus genera and estimated their ancestral haploid chromosome number. According to our inferences, these clades have an ancestral haploid chromosome number n = 15. The most recent common ancestor of Anochetus and Odontomachus has arisen between the Early Paleocene and the Early Eocene periods (time of the most recent common ancestor). In the Anochetus genus, we observed maintenance of the ancestral chromosome number estimated here in most species. This also suggests that pericentric inversions were the primary chromosomal rearrangement modulating the karyotype evolution of this genus. However, a reduction from n = 15 to n = 14 is observed in Anochetus emarginatus and Anochetus cf. madaraszi, which likely occurred by centromeric fusion. In contrast, the increase from the ancestral karyotype number in Anochetus horridus suggested centromeric fissions. Odontomachus showed maintenance of the ancestral chromosome number in the “rixosus group” and several gains in all species from the “haematodus group.” Our findings suggest that centromeric fissions and pericentric rearrangements lead to chromosomal changes in trap-jaw ants. Considering the ancestral state estimated here, changes in chromosome morphology are likely due to pericentric inversions, and chromosome number increases are likely due to centric fissions. The higher number of acrocentric or telocentric chromosomes in the karyotypes with n < 15 haploid chromosomes supports such an idea.